(untitled) (Universal International Scientific Journal, 2026)
This article discusses the role and importance of using innovative teaching methods in teaching the life and work of Boborahim Mashrab, a prominent representative of Uzbek classical literature, in secondary schools in developing students’ independent, creative, and imaginative thinking skills, based on personal experience.